Impact of a Healthy Weight Intervention Embedded Within a National Home Visiting Program on the Home Food Environment - Tabak, Rachel G.; Morshed, Alexandra B.; Schwarz, Cynthia D.; Haire-Joshu, Debra (Frontiers in Public Health, 2018)
Purpose. To determine whether a lifestyle intervention embedded within Parents as Teachers (PAT), a national child development and parenting home visiting program, helped families make food-related home environment changes. Design. Secondary data analysis of a stratified randomized pragmatic trial. (Trial Registration: This study is registered at www.clinicaltrials.gov NCT01567033) Setting. Participant homes in St. Louis, Missouri. Subjects. Women (n=179 with pre-post data, of 230 with baseline) participating in standard PAT, with overweight or obesity, and at least one preschool child with BMI percentile≥60%. Intervention. PAT+ Healthy Eating and Active Living Taught at Home (HEALTH), embedded elements of the Diabetes Prevention Program within the standard PAT curriculum. PAT+HEALTH addressed specific behaviors that impact caloric intake (e.g., sugar-sweetened beverages), focusing on behavioral and environmental strategies. Consistent with PAT practice, the frequency, number, and focus (i.e., time spent on intervention components) of home visits were determined by the family’s needs; dose structure was flexible (on average intervention: 23 [SD=9], usual care: 13 [SD=6] visits). Measures. Food availability/accessibility and distractions in the home were assessed with items drawn largely from the HomeSTEAD Survey. Analysis. Generalized estimating equations were used to test equality of changes between baseline and 24 months in the intervention and usual care groups. Results. The only significant difference in the pattern of change between usual care and intervention was soda availability/accessibility (p= 0.013). Conclusion. This embedded intervention successfully reduced availability/accessibility of sugar-sweetened beverages in the home. However, given the limited impact on other food-related home environment factors, future interventions could seek to more effectively intervene on all aspects of the home environment.